MAKNA KESEPAKATAN PARA PIHAK TERHADAP PERUBAHAN MODAL DASAR PERSEROAN TERBATAS - Yohana Feryna (University of Merdeka Malang, 2016)
The Limited Liability Company regulated by the Government shall issue Government Regulation No. 29 of 2016 concerning Changes in Authorized Capital of Limited Liability Company. The purpose of this journal is to analyze the meaning of the agreement of the parties to the Government Regulation of the Republic of Indonesia Number 29 of 2016, to know the legal consequences of changes in the amount of authorized capital of the Limited Liability Company and to formulate Article in Limited Liability Company Law concerning the amount of authorized capital of Limited Liability Company. Government Regulation of the Republic of Indonesia Number 29 the Year 2016. Government Regulation Number 29 the Year 2016 is the founders of Limited Liability Company can establish Limited Liability Company with authorized capital below fifty million rupiahs provided that the agreement of the establishment of the Limited Liability Company has reached conformity or approval by the parties in the establishment of the Limited Liability Company, the change in the capital stock regulation has the legal effect of the absence of legal protection for third parties and the absence of legal certainty.